A study on capacity development in the "What Works to Prevent Violence Against Women" programme. Issue 6 (18th August 2019) - Willan, Samantha; Kerr-Wilson, Alice; Parke, Anna; Gibbs, Andrew
ABSTRACT: While there is consensus among those working to prevent violence against women and girls of the need to develop the capacity of researchers and implementers working in the global South, there is insufficient evidence on how to effectively achieve this. This article reflects on the approaches used by the What Works programme to develop capacity. It recommends that effective capacity development requires: meaningful commitment; an organic process driven by the needs of the global South; recognising the importance of soft-skills; acknowledging what is achievable within resource constraints; and a commitment to women's rights and gender equality.